Antropologia katolicka w perspektywie ekologicznej. Studium pastoralne w świetle encykliki Laudato si - Przybyłowski, Jan Kazimierz (Collectanea Theologica, 2019)
The article presents the concept of integral Catholic anthropology with ecological elements. The source of the truth about man is Revelation and the teaching of the Church. Catholic anthropology also benefits from the achievements of modern science and is also open to ecological dialogue. Both reason and faith must be used in the search for truth. Man was created as a personal entity; therefore his task is to manage creation responsibly. Man is for himself a gift received from God and must therefore respect the natural and moral structure with he is equipped. The human person is capable of establishing personal relationships and this allows him to believe in God and to live in friendship with people and with all of creation.